CYTOTOXIC ACTIVITY AND APOPTOSIS INDUCTION OF T47D CELL LINES BY Turbinaria decurrens EXTRACT - Muhammad Nursid; nurrahmi dewi fajarningsih; Ekowati Chasanah (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2013)
Marine algae is known to contain a wide variety of biomedical compounds having pharmaceutical applications. The aim of this research was to evaluate cytotoxic activity and apoptosis induction of Turbinaria decurrens extract on T47D cell lines. Cytotoxic activity test was conducted by using MTT assay whereas detection of apoptosis was evaluated by DNA fragmentations and flow cytometry analysis. The MTT test showed that crude extract had medium cytotoxic activity to T47D, HepG2, and C28 cell lines with IC50 value of 172, againts 360 and 330 µg ml-1, respectively. After solvent partition of crude extract, the cytotoxic activity of n-hexane and ethyl acetate fractions T47D cell increased, the cytotoxic activity of n. hexane and ethyl acetate fractions T47D cell increased with IC50 value of with IC50 43.1 and 51.9 µg ml-1, respectively, whereas IC50 value of methanol fraction was 383.0 µg ml-1. Analysis of DNA fragmentation of T47D cell showed that both n-hexane and ethyl acetate fractions could not fragment DNA as a features of apoptosis. However, flow cytometry analysis by using annexin-V and propidium iodide staining revealed that n-hexane and ethyl acetate fractions could induce apoptosis in T47D cell. This research indicated that Turbinaria decurrens had potency to induce apoptosis in T47D cells.